Evaluation of interpolators for aquifer vulnerability study: The case of the Santa Maria River Basin - Luiz, Thiago Boeno Patricio; Descovi Filho, Leônidas Luiz Volcato; Silva, José Luiz Silvério da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Studies evaluating the natural vulnerability of aquifers have relevant importance for the knowledge of subject environmental contamination areas. The correct application in vulnerability maps needs constant studies, aiming the improvement of the analyzes and the development of representative maps of the studied areas. The objective of this study was to evaluate the performance of different models for the interpolation of environmental indicators of aquifer vulnerability using the kriging technique. The study was carried out in the Santa Maria River Basin by analyzing the hydrogeological aspects of 255 tube wells, located in six municipalities in the southwest of the State of Rio Grande do Sul. The data indicated that the high vulnerability class prevailed in 47,45% of the evaluated wells, followed by the medium vulnerability class corresponding to 23,14%; the low vulnerability represented 14,50%, the extreme vulnerability class corresponded to 7,85% and insignificant indicated 7,05%. The spherical, exponential, gaussian and linear models were used to interpolate the data, to define the best fit from the application of the semivariogram function. The adjustments were evaluated through the least squares method, which evidenced the best approach from the spherical model among the tested models. The spatial distribution of vulnerability demonstrated the predominance of high vulnerability in the southern portion of the municipality of Santana do Livramento, central portion of Rosário do Sul, north and northeast of São Gabriel and center of Lavras do Sul. In some areas of the basin, in municipalities of Santana do Livramento and Lavras do Sul was found the class of extreme vulnerability aquifer.